The role of selected flavonoids from bajakah tampala (Spatholobus littoralis Hassk.) stem on cosmetic properties: A review - Rut Novalia Rahmawati Sianipar; Lisman Suryanegara; Widya Fatriasari; Enos Tangke Arung; Irawan Wijaya Kusuma; Suminar Setiati Achmadi; Nur Izyan Wan Azelee; Zuratul Ain Abdul Hamid (Elsevier, 2023)
Cosmetics made from natural ingredients are increasingly popular because they contain bioactive compounds which can provide many health benefits, more environmentally friendly and sustainable. The health benefits obtained from natural-based ingredients include anti-aging, photoprotective, antioxidant, and anti-inflammatory. This article reviewed the potential of selected flavonoids from bajakah tampala (Spatholobus littoralis Hassk.) as the native plant in Indonesia. We present in silico, in vitro, in vivo, and clinical research data on the use of selected flavonoids that have been reported in other extracts.